The Moderating Role of Institutional Climate on the Relationship between Job Satisfaction and Deviant Behavior. Issue 5 (4th May 2023) - Dewangan, Rashmi; Verghese, Manoj
ABSTRACT: The purpose of this study is to analyze the relationship between job satisfaction and deviant behavior in workplace. Along with this, a major motivation behind this research work is to assess the role of institutional climate on the beforementioned relationship. In line with this, four dimensions of institutional climate namely, academic, administrative, developmental, and financial climate have been taken into consideration. Primary data collected from 357 respondents via e-mail survey have been analyzed in this study. The target population of this study are faculties and academicians employed in the field of technical education. The data have been analyzed by measurement model assessment and structural model assessment. Multigroup analysis has been used for studying the moderating role of institutional climate. The results establish that job satisfaction strongly influences deviant behavior. These are inversely related, i.e., an increase in job satisfaction would result in less deviant behavior. The more satisfied an employee is with his/her job, deviant behavior would reduce in them. The study also finds that institutional climate moderates the relationship between job satisfaction and deviant behavior. Amongst the different dimensions of institutional climate, it is observed that individuals who think negative about their financial climate may turn deviant quicker and by a far greater magnitude. Thus, financial climate came out to be the most influencing moderators amongst its peers academic, administrative, and developmental climates.